TIR Domain-Containing Adaptor-Inducing Interferon-β (TRIF) Participates in Antiviral Immune Responses and Hepatic Lipogenesis of Large Yellow Croaker (Larimichthys Crocea) - Zhu, Si; Xiang, Xiaojun; Xu, Xiang; Gao, Shengnan; Mai, Kangsen; Ai, Qinghui (Frontiers in Immunology, 2019)
TIR domain–containing adaptor-inducing interferon- (TRIF), a cytosolic adaptor protein, plays a key role in mammalian toll like receptors-mediated signaling pathway. However, the role of TRIF in large yellow croaker (LycTRIF) remains poorly understood. The main objective of this study was to explore the role of LycTRIF in triggering antiviral immune responses and the potential function of LycTRIF in regulating lipid metabolism. In the present study, the full-length coding sequence of TRIF from large yellow croaker was cloned and characterized. In vivo, upon poly (I:C) stimulation, the transcriptional levels of LycTRIF were rapidly elevated in immune related tissues at early stage of injection. In vitro, mRNA expression of LycTRIF were significantly but not dramatically up-regulated in macrophages treated with poly (I:C). Activation of LycTRIF by poly (I:C) significantly increased the transcription of genes involved in inflammatory responses, and such induction was blocked by knockdown of LycTRIF. What’s more, the ability of LycTRIF to induce inflammatory responses may partially attributed to the promoting of mRNA expression of IFNh and NF-B pathways. In addition, activation of LycTRIF-mediated pathway inhibited the increase of hepatic stearoyl–coenzyme A (CoA) desaturase 1 abundance induced by palmitic acid and subsequently alleviated the lipid accumulation in hepatocytes. These results revealed the crucial role of LycTRIF in triggering antiviral immune responses and the unconventional metabolic function of LycTRIF in regulating hepatic lipogenesis of large yellow croaker.